1999
DOI: 10.1152/ajprenal.1999.276.5.f658
|View full text |Cite
|
Sign up to set email alerts
|

Localization of PEPT1 and PEPT2 proton-coupled oligopeptide transporter mRNA and protein in rat kidney

Abstract: To determine the renal localization of oligopeptide transporters, Northern blot analyses were performed and polyclonal antisera were generated against PEPT1 and PEPT2, the two cloned rat H+/peptide transporters. Under high-stringency conditions, a 3.0-kb mRNA transcript of rat PEPT1 was expressed primarily in superficial cortex, whereas a 3.5-kb mRNA transcript of PEPT2 was expressed primarily in deep cortex/outer stripe of outer medulla. PEPT1 antisera detected a specific band on immunoblots of renal and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
168
1
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(183 citation statements)
references
References 18 publications
13
168
1
1
Order By: Relevance
“…mRNA expression studies in rat (11) have demonstrated that while PEPT1 is specific for early regions of the proximal tubule (pars convoluta), PEPT2 is overwhelmingly but not exclusively expressed in latter regions of the proximal tubule (pars recta). More recent studies (12) have corroborated these findings and provided definitive evidence for the heterogeneous distribution of PEPT1 and PEPT2 proteins in rat kidney. In this regard, strong PEPT1-specific immunostaining was observed in outer cortex, with progressively weaker staining in deeper cortical regions and no staining in outer medulla.…”
Section: Uptake Of Glysar In Bbmv: Outer Cortex Vs Outer Medulla Stumentioning
confidence: 60%
See 1 more Smart Citation
“…mRNA expression studies in rat (11) have demonstrated that while PEPT1 is specific for early regions of the proximal tubule (pars convoluta), PEPT2 is overwhelmingly but not exclusively expressed in latter regions of the proximal tubule (pars recta). More recent studies (12) have corroborated these findings and provided definitive evidence for the heterogeneous distribution of PEPT1 and PEPT2 proteins in rat kidney. In this regard, strong PEPT1-specific immunostaining was observed in outer cortex, with progressively weaker staining in deeper cortical regions and no staining in outer medulla.…”
Section: Uptake Of Glysar In Bbmv: Outer Cortex Vs Outer Medulla Stumentioning
confidence: 60%
“…These investigators and others (9,10) have shown that while PEPT1 is expressed in the intestine and to a smaller extent in kidney, PEPT2 is expressed only in kidney. In addition, more recent studies (11,12) have demonstrated that PEPT1 and PEPT2 are differentially distributed along the proximal tubule, with PEPT1 being predominant in the convoluted segment and PEPT2 being predominant in the straight segment. However, mRNA and/or protein expression levels do not always reflect a similar degree of substrate activity.…”
Section: Introductionmentioning
confidence: 98%
“…It was then also found in the brush-border membrane of epithelial cells in the kidney proximal tubule S1 segment (60). By immunostaining and transport analysis, PEPT1 has also recently been shown to be present in the apical membrane of bile duct epithelial cells (36).…”
Section: Tissue Distribution Of Pept1 and Pept2 And Their Tubular Locmentioning
confidence: 97%
“…It was initially cloned from a renal cDNA library and detected in brush-border membranes of cells in S2 and S3 segments (10,60). More recently, PEPT2 has been identified in the peripheral nervous system, in the membranes and cytoplasm of satellite glial cells surrounding the ganglionic neurons (29), and in the central nervous system.…”
Section: Tissue Distribution Of Pept1 and Pept2 And Their Tubular Locmentioning
confidence: 99%
“…The specificity of hPepT1 is broad and includes many di-and tripeptides in addition to various peptide-derived drugs (3)(4)(5)(6)(7)(8). PepT1 is mainly expressed in brush-border membranes of enterocytes in the small intestine, in proximal tubular cells of the S1 segment of the kidney, and in bile-duct epithelial cells (4,5,(9)(10)(11)(12)(13)(14)(15). By contrast, in the colon, expression of PepT1 mRNA and protein is low (16) and sometimes cannot be detected (10,15,17).…”
Section: Introductionmentioning
confidence: 99%